2010
DOI: 10.2326/osj.9.141
|View full text |Cite
|
Sign up to set email alerts
|

Mating Advantage of Multiple Male Ornaments in the Barn SwallowHirundo Rustica Gutturalis

Abstract: The maintenance of multiple ornaments by animals can be explained when those multiple ornaments are sexually selected. However, there have been only a few studies of sexual selection on multiple ornaments. We investigated sexual selection on two ornaments, plumage coloration and white spots in the tail, in a population of Barn Swallows Hirundo rustica gutturalis in Japan. There was sexual dimorphism in throat coloration and in the size of the white spots in the tail. Males with a less saturated (colourful) thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 40 publications
(45 reference statements)
1
65
0
Order By: Relevance
“…Then, I present how consideration (or ignorance) of inconspicuous male traits affects our understanding of evolution of overall male phenotype with a simple hypothetical scenario. Interrelationships among male traits Several studies have demonstrated positive intercorrelations among male secondary sexual characteristics in barn swallows (e.g., Møller et al 1998a;Saino et al 2003;Hasegawa et al 2010a; but see Vortman et al 2011;Safran et al 2016 for no detectable relationships). Still, it is often unclear whether these patterns reflect evolutionary covariation without a well-designed experiment (e.g., Wagner et al 2012;van Noordwijk and de Jong 1986;Stearns 1992;Andersson et al 2002;Saino et al 2003), due to individual variation in resource availability (e.g., when the allocation between the traits varies less than the total investment, a positive correlation can be predicted even if there is a trade-off between two ornaments).…”
Section: Importance Of Inconspicuous Male Traits On Overall Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…Then, I present how consideration (or ignorance) of inconspicuous male traits affects our understanding of evolution of overall male phenotype with a simple hypothetical scenario. Interrelationships among male traits Several studies have demonstrated positive intercorrelations among male secondary sexual characteristics in barn swallows (e.g., Møller et al 1998a;Saino et al 2003;Hasegawa et al 2010a; but see Vortman et al 2011;Safran et al 2016 for no detectable relationships). Still, it is often unclear whether these patterns reflect evolutionary covariation without a well-designed experiment (e.g., Wagner et al 2012;van Noordwijk and de Jong 1986;Stearns 1992;Andersson et al 2002;Saino et al 2003), due to individual variation in resource availability (e.g., when the allocation between the traits varies less than the total investment, a positive correlation can be predicted even if there is a trade-off between two ornaments).…”
Section: Importance Of Inconspicuous Male Traits On Overall Phenotypementioning
confidence: 99%
“…By contrast, in colonial populations in which nest predation is virtually absent, choosing attractive mates produces high-quality offspring. Such benefits of choosing attractive males should increase with female preference for the trait through a runaway process, particularly in dense colonial populations due to the high frequency of extra-pair young (> 15% of nestlings: reviewed in Table 5.1 in Turner 2006; see Hasegawa et al 2010a for sparse populations where extra-pair paternity is virtually absent: < 3%), which boosts sexual selection (e.g., eightfold compared to no extra-pair paternity: Kleven et al 2006). At the same time, because courtship display at breeding sites is not necessary for extrapair paternity (e.g., Hasegawa et al 2016a; also see Turner 2006), total female preference (and selection) for the traits displayed during courtship (e.g., territory, enticement calls; see Fig.…”
Section: Interrelationship Among Female Mate Preferencesmentioning
confidence: 99%
“…We used skin specimens that were collected during the breeding season (i.e., from April to August; Hasegawa et al 2010;reviewed in Turner 2006) to exclude migrating or wintering swallows. In total, we examined 65 skins of adult barn swallows from six museums.…”
Section: Study Specimensmentioning
confidence: 99%
“…Because of the difficulty in measuring from the skin specimens, we used indices that were somewhat different from those used for live birds (see Hasegawa et al 2010). The tail fork depth was used instead of the tail length for the easiness and preciseness of measurements, as the tail fork depth of males also increases from south to north at least in Europe (Møller 1995;Møller et al 1995;Barbosa and Møller 1999;reviewed in Turner 2006, p. 24).…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation